DERİ LEZYONLARINDAN AYRILAN BİR CRYPTOCOCCUS NEOFORMANS KÖKENİ - KANTARCIOĞLU, A. Serda; YÜCEL, Ayhan (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Cryptococcus neoformans is an encapsulated pathogen fungus that can cause cryptococcosis rarely in completely healty individuals and commonly in immunosuppressed patients by inhalation into the lungs and than spreading hematogenously to the central nervous system, bone and joint, eye, prostate and other body sites. In this survey, specimens from cutaneous lesions, urine and blood from a patient previously diagnosed Trombotic Trombocytopenic Purpura were mycologycally examined and antifungal susceptibility tests of the isolated strain were carried on according to NCCLS M27-A macrobroth method along with the experimental infection in mices. Results.- The fungus strain isolated from specimens was identified as Cryptococcus neoformans. The strain was found susceptible to fluconazole, itraconazole, ketoconazole and miconazole and resistant to flucytosin. MIC values obtained against Amphotericin B and terbinafine were respectively 1 mg/ml, and 4 mg/ml. Conclusion.- This study was presented in view of limited number of isolations of C. neoformans in Turkey, isolated from cutaneous lesions and the first clinical isolate in vitro susceptibility against seven conventional antifungal agents was carried on according to NCCLS reference M27-A macrobroth method.